Pengembangan Sistem Informasi Geografis Untuk Penentuan Tingkat Kenyamanan Rute Bagi Pejalan Kaki Lingkup Kampus Universitas Brawijaya - Ahmad Zaky Syihan; Alfi Nur Rusydi; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Brawijaya University is one of the biggest campus located in Malang city. In daily basis, there is a lot of people doing their activities by walking in campus area. From many walking activities, the comfort level of pedestrian routes needs to be considered. But there is no data that can represent the level of comfort in pedestrian routes throughout the University of Brawijaya. To determine the comfort level of pedestrian routes in the entire University of Brawijaya, it needs spatial analysis with the development of geographic information system that can produce information about the comfort level of pedestrian routes in the entire University of Brawijaya. To obtain information about the comfort level of pedestrian routes, data acquisition activities is needed in the form of aerial photography and road networks. The acquired data is then processed using the semi automatic classification method to obtain wide canopied vegetation distribution data, which is a determining factor in the comfort level of pedestrian routes in this study. Then the data will be implemented into the system that can be accessed by pedestrians in Universitas Brawijaya to obtain the information. Geographical information systems are then tested using black box and user acceptance testing. It Obtained 100% black box test results which states that the system can fulfill all the user requirements. In user acceptance testing, the overall result is 83.83% which describes the user can receive the system well in the three criteria tested, namely performance, usability, and accuracy.